Agar gel strength: A correlation study between chemical composition and rheological properties. (15th January 2020) - Bertasa, Moira; Dodero, Andrea; Alloisio, Marina; Vicini, Silvia; Riedo, Chiara; Sansonetti, Antonio; Scalarone, Dominique; Castellano, Maila
Graphical abstract: Highlights: Raw agars have a different amount of anhydro units, responsible for gel strength. The greater the amount of anhydro units, the greater the mechanical performances. The strength of agar gels increases with increasing the polymer concentration. The annealing process promotes the formation of additional crosslinking points. Addition of the chelating agent leads to an enhancement of the gel stiffness. Abstract: Agar is a natural polymer commonly used in various fields of application ranging from cosmetics to the food industry. In particular, for over forty years agar gels have been used in the field of conservation of Cultural Heritage where they are considered as one of the main well-performing tools in cleaning procedures. In the present work, the relation between the chemical composition and the mechanical strength of four different agar hydrogels was evaluated by comparing the results obtained via pyrolysis-gas chromatography/mass spectrometry and rheological characterization. Agar composition was studied by means of a pyrolysis-gas chromatography/mass spectrometry approach in order to differentiate the anhydrous, galactose and glucose units. Pristine agar gels, gels after double annealing, and gels with and without chelating agent were studied by means of amplitude, frequency and time sweep rheological tests to evaluate all the preparation approaches commonly used by conservators, also taking into account changes in the transparency via UV–vis spectroscopy. A high percentage of anhydrous units in the polymer backbone was found to provide superior mechanical stiffness to the pristine hydrogels, even if it did not seem to affect their long-term stability. The annealing process significantly improved the rheological response of galactose-rich agar hydrogels being able to promote the establishment of additional crosslinking points, whereas the additive presence showed to improve the hydrogel stiffness owing to a more structured polymer network. Moreover, the progressive reduction of the impurities and/or network defects within the hydrogels occurring due to the annealing process slightly increased the transparency of the hydrogels, which is an important aspect for applications in the conservation of Cultural Heritage.